Evaluation of natural regeneration of Pinus sylvestris L. on burnt areas in arid steppe climate conditions - Lyavdanskaya Ol'ga; Bastayeva Galiya; Kubasov Andrey; Nesvat Aleksandr; Suleymenova Raislu (BIO Web of Conferences)
The article presents the results of assessing the success of natural forest restoration of Scots pine in areas affected by crown fires in the conditions of the sharply continental climate of the steppes. The amount of Pinus sylvestris L. undergrowth was calculated by height groups, and its reliability was assessed in accordance with size categories. The vector of restoration of natural vegetation on burnt areas in steppe conditions is considered, in the presence of a seed bank of Scots pine. The features of restoration of post-fire vegetation as the most important element of bioecological monitoring are studied. The number of species of accompanying steppe herbaceous species constituting the basis of the flora of the studied object is established. The ecological features and degrees of detection of formation of vegetation after fire, as well as indirect information on possible mechanisms underlying the dynamics of diversity associated with the characteristics of natural and climatic conditions, are revealed, practical recommendations are given to promote the restoration of Pinus sylvestris L. in areas affected by forest fires in the conditions of the arid climate of the steppes.